2019
DOI: 10.3390/toxins11020066
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Periocular Botulinum Neurotoxin on the Tear Film Homeostasis and the Ocular Surface Change

Abstract: Clinical usage of botulinum neurotoxin (BoNT) in ophthalmology has dramatically increased since the 1980s and has become one of the most widely used agents for treating facial movement disorders, autonomic dysfunction and aesthetic wrinkles. Despite its high efficacy, there are some complications with periocular BoNT injections due to its chemodenervation effect. Among these, there is still controversy over the BoNT effect on tear film homeostasis and the ocular surface. A periocular BoNT injection could dry t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…Few studies investigating only affected eyes of HFS patients showed that the injection of BTX-A caused decreased tear film stability and decreased Schirmer test, especially in patients received lateral injection sites. 5 , 7 , 14 Mitigating effects including an increase in tear meniscus height, reduction of mean blink output, an increase in lipid tear thickness, and an increased TBUT following BTX-A injection were also observed from the other studies with similar design. 5 , 7 , 12 To the best of our knowledge, only a study by Pellegrini et al had non-affected eye as a comparison and found a significant lower of TBUT at 1 month after injection of BTX-A in affected eye, but no significant change in non-affected eye among HFS patients who received long-term BTX-A injections.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Few studies investigating only affected eyes of HFS patients showed that the injection of BTX-A caused decreased tear film stability and decreased Schirmer test, especially in patients received lateral injection sites. 5 , 7 , 14 Mitigating effects including an increase in tear meniscus height, reduction of mean blink output, an increase in lipid tear thickness, and an increased TBUT following BTX-A injection were also observed from the other studies with similar design. 5 , 7 , 12 To the best of our knowledge, only a study by Pellegrini et al had non-affected eye as a comparison and found a significant lower of TBUT at 1 month after injection of BTX-A in affected eye, but no significant change in non-affected eye among HFS patients who received long-term BTX-A injections.…”
Section: Discussionmentioning
confidence: 56%
“… 5 , 7 , 14 Mitigating effects including an increase in tear meniscus height, reduction of mean blink output, an increase in lipid tear thickness, and an increased TBUT following BTX-A injection were also observed from the other studies with similar design. 5 , 7 , 12 To the best of our knowledge, only a study by Pellegrini et al had non-affected eye as a comparison and found a significant lower of TBUT at 1 month after injection of BTX-A in affected eye, but no significant change in non-affected eye among HFS patients who received long-term BTX-A injections. 11 Our insignificant observations on tear dynamic with a unique design including naïve and long-term BTX-A injection of HFS patients added to the pool of conflicting evidence of the BTX-A effect on tear dynamic.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…1,[6][7][8] However, the effect of BTX-A injections on the ocular surface remains controversial: while some studies reported improvement, some reported worsening or no change in tear film parameters after BTX-A applications. [8][9][10][11][12][13][14][15][16] In this study, the authors aimed to objectively assess EB patients regarding the effect of botulinum toxin injections on the ocular surface, assessing tear meniscus area with optical coherence tomography. Break-up time (BUT), Schirmer test, and the Ocular Surface Disease Index (OSDI) questionnaire were also evaluated at baseline and after BTX-A injections.…”
mentioning
confidence: 99%